Konflik Agraria dan Ketimpangan Struktur Kepemilikan Tanah: Studi Kasus Perkebunan Sawit di Kalimantan Tengah - L, Leon; Ramadhan, Adam; Dewani, Citranti Hanifah; Farhan, Fien Naufal Zaim; Winanti, Atik (Media Hukum Indonesia (MHI), 2025)
Agrarian conflicts in Indonesia are structural issues rooted in the unequal distribution and ownership of land. This study examines the dynamics of agrarian conflict in Central Kalimantan, particularly related to the expansion of oil palm plantations and its impact on local land ownership structures. Using a juridical-sociological approach and a case study method, the research finds that the implementation of the Basic Agrarian Law (UUPA) has not yet fully realized the principles of social justice in agrarian resource management. The disparity in land ownership between corporations and indigenous communities is identified as a major trigger for prolonged conflict. This study recommends the enforcement of the core principles of the UUPA and the strengthening of indigenous land rights within national agrarian policy.